Determination of CYP2C19 Polymorphism, Side Effects, and Medication Adherence in Patients Who have Utilized Selective Serotonin Reuptake Inhibitors - (:unkn) unknown (My University, 2016)
0

Objective: The aim of this study is to determine relationship of cytochrome P-450 2C19 (CYP2C19) enzymes polymorphism, side effects, and medication adherence in patients who have been diagnosed with major depression and have utilized selective serotonin reuptake inhibitors. Methods: Fifty-three major depression patients (mean of age: 33.25±11.29 years old; male/female: 7/46) were included in this study. Polymorphisms were determined from genomic DNA by using the 'Real-Time Polymerase Chain Reaction' method. Side effects and medication adherence levels were assessed by using the 'Toronto Side Effects Scale' and the four items medication adherence scale (Morisky, Green and Levine), respectively. Results: The most common side effects that patients reported were drowsiness/daytime somnolence (54.7%), malaise or fatigue (43.4%), sweating (43.4%), nausea (41.5%) and dry mouth (41.5%). Only nine (17%) patients were found to be highly adherent to their medication. When evaluating the CYP2C19 polymorphisms of patients, 37.7%, 24.5% and 20.8% of the patients were classified as intermediate, extensive and ultra-rapid metabolizers, respectively. Allele frequencies of CYP2C19*17 and CYP2C19*2 was calculated as 24.5% and 27.4%, respectively. Although there were some differences in side effect scores and medication adherences among the polymorphism groups, these relationships were not found to be statistically significant. Conclusion: This study shows that patients who utilized antidepressants frequently experienced side effects and had low medication adherence. Another interesting finding is the high rate of ultrarapid metabolizers of CYP2C19
Keywords: Farmakoloji ve Eczacılık